Pembelajaran Fisika Mengintegrasikan Etnosains Makanan Tradisional (Literatur Review) - Nurmaliati, Nurmaliati (JURNAL PENDIDIKAN ROKANIA, 2024)
This study aims to determine traditional foods that can be integrated into physics learning materials and to determine competencies that can be improved through learning traditional food ethnoscience. This research method is a literature review method, with a sample of 9 research articles from national and international journals. From the results of the study, it is known that among the traditional foods that can be integrated into physics learning, namely, Sago, Tempe, Pempek, Srabi, Tape, Terasi, Rawon, Fish Smoked and Javanese Noodles. These traditional foods are integrated into physics learning on matter, force, pressure, momentum, temperature and heat and energy. Traditional food is integrated into physics learning in the form of modules and LKPD. The integration of traditional food into physics learning can improve the competence of students on learning outcomes, science process skills and scientific literacy of students.